Pharmacological interventions for people with borderline personality disorder - Stoffers-Winterling, Jutta M.; Storebø, Ole Jakob; Völlm, Birgit A.; Mattivi, Jessica T.; Nielsen, Signe Sofie; Kielsholm, Maja Laerke; Faltinsen, Erlend G.; Simonsen, Erik; Lieb, Klaus (Wiley, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the beneficial and harmful effects of pharmacological treatment for adolescents and adults with borderline personality disorder (BPD).